Acquisition of the syntax–discourse interface: The expression of point of view - Lillo-Martin, Diane (2011)
This study examines the proposal that the syntax–discourse interface is particularly vulnerable, and therefore components of this interface are acquired later than those of the syntax–semantics interface. The proposal is examined using data from the native language acquisition of markers of point of view in American Sign Language and Brazilian Sign Language, known as constructed action (CA). CA was observed in the spontaneous production of two case studies from as early as 1 year, 7 months of age, with the correct eye-gaze, facial expression, and manner of movement. However, the children sometimes failed to indicate the referent whose point of view was being expressed, and were not skilled at maintaining point of view marking across discourse. The results are interpreted as providing support for the vulnerability of the syntax–discourse interface, and for the interpretation of this vulnerability in connection with children’s relatively poor ability to assume an identical discourse context with their interlocutor.